Transfer of Agricultural Land Function in relation to Spatial Law on - Yusuf Efendi; Mohammad Roesli; Asep Heri (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
The purpose of this study is to analyze the legal procedures for permitting land use change in the perspective of administrative law. space, in terms of reviewing positive law and the strength of the influence of laws and regulations, reviewing positive law in terms of legal effectiveness. The research method uses a normative juridical research method, which focuses on the study starting from the provisions of the applicable laws and regulations, accompanied by legal theories and principles related to the problems studied. Thus, this research refers to the laws and regulations with a descriptive analytical discussion, which focuses on solving actual problems by collecting legal materials, compiling, classifying, and then analyzing them. Agricultural land products have received protection in accordance with the ratification of Law no. 41 of 2009 and this is also reinforced by Presidential Regulation No. 59 of 2019 concerning controlling land use change, but in reality population growth and the need to live together with development are rife being built regardless of the concept of being environmentally intelligent. but in concept the existing legal regulations are still based on large entrepreneurs with high production capacity which suppress the compulsion of rural farmers who are far from government administration.